Research on influencing factors of soybean yield in China’s northeast black soil region based on PLS-SEM - Tan, Yuping; Wang, Zhiqiang (Frontiers in Sustainable Food Systems, 2024)
Soybean yield is affected by soil, terrain, biology, and other factors. However, few studies have considered the main and secondary influencing factors of soybean yield and the interaction mechanisms among these factors within a catchment area in the black soil region. This study aims to explore the main influencing factors and the coupling mechanisms affecting soybean yield in China's northeast black soil region. Using 46 samples from Heshan Farm, Nenjiang City, a driving factor model for soybean yield was developed using PLS-SEM, incorporating latent variables such as soybean yield, topographic characteristics, soil physical properties, soil chemical properties, and biological factors. The main factors, secondary factors, and their interactions affecting soybean yield were discussed. Topographic factors, soil physical properties, and soil chemical properties had positive total effects on soybean yield, while biological factors had a direct negative impact on soybean yield, with the total effects ranging from soil physical properties > biological factors > topographic factors > soil chemical properties. In terms of soil physical properties, the load value of soil bulk density was the largest (-0.917). This was followed by saturated water content (0.886), total porosity (0.855), capillary water holding capacity (0.837), field water holding capacity (0.763), black soil thickness (0.695), sand particle size (-0.664), clay particle size (0.450), and gravel ratio (-0.439). These findings demonstrate soil physical properties are the key factors affecting soybean yield. Thus, soil improvement in small catchment, by reducing bulk density, increasing porosity, and improving soil water retention capacity are key to improving soybean yield.